Whole seed lentil flours from different varieties (Brewer, Crimson, and Richlea) demonstrated significant variations in their expansion characteristics during extrusion. Issue 3 (10th February 2021) - Ek, Pichmony; Gu, Bon‐Jae; Ganjyal, Girish M.
Abstract : Abstract: The properties of flours and extrusion characteristics, of three lentil varieties (Brewer, Crimson, and Richlea) were studied. The effects of barrel temperature (110, 125, and 140 °C) and screw speed (150, 200, and 250 rpm) on process responses and extrudate characteristics were evaluated using a corotating twin‐screw extruder. The three varieties of lentils had significant differences ( p < 0.05) in their starch (48.7% to 50.9%), protein (20.4% to 22.7%), and fat content (1.3% to 1.9%), gelatinization temperature (71.7 to 74.6 °C), peak viscosity (123.3 to 179.7 mPa.s), and melting temperature (113.6 to 119.7 °C). The lentil variety, barrel temperature, and screw speed significantly impacted the process responses and extrudate properties. Whole lentil flours exhibited the highest expansion ratio (3.0 to 3.6) at the lowest temperature (110 °C) and the highest screw speed (250 rpm). Richlea variety had the highest expansion ratio (3.6) and the highest water solubility index (45.4%) as it had the highest starch content and peak viscosity, and the lowest protein content and melting temperature. Meanwhile, Brewer variety exhibited the lowest expansion ratio (1.9 to 3.0) compared to Richlea (2.5 to 3.6) and Crimson (2.4 to 3.0) in most of the extrusion conditions studied. Richlea variety was the most suitable for making direct‐expanded extrudates among the varieties studied. The significant differences in the properties of flours from the three varieties of lentils resulted in significant impacts on the properties of their extrudates. Therefore, determining the properties of flours of different varieties is useful to select the appropriate varieties for extrusion processing. Practical Application: The information from this study is useful for the food industry to select the appropriate lentil varieties and processing conditions for the development of direct‐expanded products. The data prove the importance of understanding the chemical composition, pasting, and thermal properties to select the appropriate varieties for extrusion processing.